Nitrates in the treatment of patients with coronary artery disease: focus on isosorbide dinitrate - V. P. Lupanov (Медицинский совет, 2015)
The article tells about the pharmacology of nitrates and their place in comprehensive treatment of coronary artery disease. The mechanisms of action of organic nitrates, specifically the short-acting metered dose spray isosorbide dinitrate (ID), are demonstrated. Indications and contraindications for use in various forms of coronary artery disease are analyzed.